2012
DOI: 10.1038/nature11121
|View full text |Cite
|
Sign up to set email alerts
|

An abundance of small exoplanets around stars with a wide range of metallicities

Abstract: The abundance of heavy elements (metallicity) in the photospheres of stars similar to the Sun provides a 'fossil' record of the chemical composition of the initial protoplanetary disk. Metal-rich stars are much more likely to harbour gas giant planets, supporting the model that planets form by accumulation of dust and ice particles. Recent ground-based surveys suggest that this correlation is weakened for Neptunian-sized planets. However, how the relationship between size and metallicity extends into the regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

85
709
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 691 publications
(807 citation statements)
references
References 25 publications
85
709
2
3
Order By: Relevance
“…In the last four years, the Kepler mission yielded over 4000 exoplanet candidates, most of them with sizes smaller than Neptune and down to Earth-sized planets. Such small planets (Super Earths) have been shown to be abundant and even to constitute the majority of exoplanets (Buchhave et al, 2012;Batalha et al, 2013). Further work has demonstrated that such planets are often found within the Habitable Zone (HZ) of their host star.…”
Section: Prevalence Of Earthlike Planets Outside Of the Solar Systemmentioning
confidence: 99%
“…In the last four years, the Kepler mission yielded over 4000 exoplanet candidates, most of them with sizes smaller than Neptune and down to Earth-sized planets. Such small planets (Super Earths) have been shown to be abundant and even to constitute the majority of exoplanets (Buchhave et al, 2012;Batalha et al, 2013). Further work has demonstrated that such planets are often found within the Habitable Zone (HZ) of their host star.…”
Section: Prevalence Of Earthlike Planets Outside Of the Solar Systemmentioning
confidence: 99%
“…In fact, from examination of the ∼150000 stars in the target list of the Kepler Mission it can be asserted that the fraction of stars showing likely planetary transits is a few per cent. No particular requirement for host star composition appears required for planetary formation (Buchave et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…They reported an asteroseismically determined stellar radius R * = 1.081±0.019 R e , stellar mass M * = 1.069±0.048 M e , and surface gravity log g = 4.399±0.012. Additionally, Huber et al (2013) use Stellar Parameter Classification (SPC, Buchhave et al 2012Buchhave et al , 2014 on spectra from Keck-HIRES (Vogt et al 1994), the TRES spectrograph on the 1.5 m at Whipple Observatory (Furesz 2008) and the Tull spectrograph on the 2.5 m at McDonald Observatory (Tull et al 1995), to obtain a metallicity of [Fe/H] = 0.350±0.101 and effective temperature T eff = 5739±75 K. McQuillan et al (2013) searched for the stellar rotation period of KOI-273 in the autocorrelation function of the Kepler photometry and were unable to detect it.…”
Section: Introductionmentioning
confidence: 99%